2012
DOI: 10.1584/jpestics.d11-032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of percolation flow on herbicide loss from rice paddies

Abstract: e fate and transport of pretilachlor, one of the most widely used rice-paddy herbicides in Japan, were monitored in a rice paddy plot for 28 days a er its application in the ve study years. e e ect of the percolation rate on herbicide loss was investigated.e concentration of pretilachlor in the paddy water was at its highest level within 2 days of application. e maximum concentration in percolated water was lower, and it was reached 1 or 2 days later than that in the paddy water. Almost all the pretilachlor lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…In contrast, the peak time of the simulated concentrations with consideration of the seepage process and excluding adsorption and desorption kinetics (Case 2) coincided with that of the observed concentrations. This is in agreement with results reported by Sudo et al,16) in which the increase in the concentration of pretilachlor in horizontal percolation water was observed immediately after application. However, the simulated results overestimated the measured concentrations for bromobutide and daimuron.…”
Section: Results and Disscussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, the peak time of the simulated concentrations with consideration of the seepage process and excluding adsorption and desorption kinetics (Case 2) coincided with that of the observed concentrations. This is in agreement with results reported by Sudo et al,16) in which the increase in the concentration of pretilachlor in horizontal percolation water was observed immediately after application. However, the simulated results overestimated the measured concentrations for bromobutide and daimuron.…”
Section: Results and Disscussionsupporting
confidence: 93%
“…20) However, the seepage pathway defined in this study is provisional, and it is difficult to adequately consider the preferential water flow pathways through macropores and cracks in bund soil reported previously 16) for an advection-diffusion model. Therefore, a compartmentalized approach was employed in this study.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Slower movement may decrease the concentration in the percolation water; however, the concentration derived from percolation of the paddy water in the high-concentration period may have remained high in a drainage canal. Sudo et al 26) also reported that the concentration of the herbicide pretilachlor in percolation water a week after application was observed to be higher than that in paddy water.…”
Section: Herbicide Concentration In the Percolation Flow And Distribu-mentioning
confidence: 96%
“…24) A number of studies have estimated pesticide discharge by surface runoff; however, studies using field observations and model simulations that focus on discharge by percolation are limited. Sudo et al 26) reported that the cumulative loss of the herbicide pretilachlor due to lateral percolation flow from a single paddy plot ranged from 7.4 to 16.3% of the applied mass and the loss increased proportionally with the percolation flow rate. Inao et al 27) reported an improved PADDY-Large model including lateral-seepage pesticide loss through bunds, which successfully simulated the temporal changes in pesticide concentrations in a river drainage system.…”
Section: Introductionmentioning
confidence: 99%